2019
DOI: 10.1016/j.bja.2019.03.045
|View full text |Cite
|
Sign up to set email alerts
|

The association between postoperative cognitive dysfunction and cerebral oximetry during cardiac surgery: a secondary analysis of a randomised trial

Abstract: Background: Postoperative cognitive dysfunction (POCD) occurs commonly after cardiac surgery. Near-infrared spectroscopy (NIRS) has been used to monitor regional cerebral oxygen saturation (rScO 2) in order to minimise the occurrence of POCD by applying dedicated interventions when rScO 2 decreases. However, the association between rScO 2 intraoperatively and POCD has not been clarified. Methods: This is a secondary analysis of a randomised trial with physician-blinded NIRS monitoring and cognitive testing at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 36 publications
2
49
1
Order By: Relevance
“…Patients with manifest neurologic incumbencies who were exposed to low rSO 2 during cardiopulmonary bypass (CPB) 11,22 could potentially have elevated biomarkers, but the CPB wash‐out effect could obliterate such results. Similarly, POCD incidence was not different in CPB patients grouped according to rSO2 profile (high‐ vs. low saturation), presumably because all patients had equal microcirculatory shortcomings undifferentiated by NIRS 27 . Our data reveal, perhaps merely an indication, that a previously unreported significant association between tau elevation and POCD z‐scores, exists.…”
Section: Discussionmentioning
confidence: 46%
“…Patients with manifest neurologic incumbencies who were exposed to low rSO 2 during cardiopulmonary bypass (CPB) 11,22 could potentially have elevated biomarkers, but the CPB wash‐out effect could obliterate such results. Similarly, POCD incidence was not different in CPB patients grouped according to rSO2 profile (high‐ vs. low saturation), presumably because all patients had equal microcirculatory shortcomings undifferentiated by NIRS 27 . Our data reveal, perhaps merely an indication, that a previously unreported significant association between tau elevation and POCD z‐scores, exists.…”
Section: Discussionmentioning
confidence: 46%
“…However, NIRS is believed to be best used as a trend monitor, without following strict thresholds [19]. It seems to be better for recognizing patients at risk than guiding interventions [20].…”
Section: Discussionmentioning
confidence: 99%
“…In the latter studies, in the intervention group, cerebral StO 2 was monitored during the surgical operation by NIRS, and supplemental oxygen dosage was adjusted according to StO 2 level, while in the control group, the treatment was not directed by NIRS readings. In several studies, the intervention group demonstrated a decreased incidence of adverse events compared with the control group [ 145 , 146 , 147 ], while in similar studies [ 148 , 149 , 150 ], the NIRS-guided intervention was not associated with improved patient outcomes. Yu et al [ 151 ], in a systematic review, inferred low quality of evidence for the beneficial effect of cerebral NIRS monitoring on postoperative adverse events, such as stroke, delirium or death, due to a low number of events and wide confidence intervals.…”
Section: Near Infrared Spectroscopy (Nirs)mentioning
confidence: 99%